The Rachel Incident - O'Donoghue, Caroline (Alfred A. Knopf, 2023)
"Rachel is a student working at a bookstore when she meets James, and it's love at first sight. Effervescent and insistently heterosexual, James soon invites Rachel to be his roommate and the two begin a friendship that changes the course of both their lives forever. Together, they run riot through the streets of Cork city, trying to maintain a bohemian existence while the threat of the financial crash looms before them. When Rachel falls in love with her married professor, Dr. Fred Byrne, James helps her devise a reading at their local bookstore, with the goal that she might seduce him afterwards. But Fred has other desires. So begins a series of secrets and compromises that intertwine the fates of James, Rachel, Fred, and Fred's glamorous, well-connected, bourgeois wife."--